LIGHT PREFERENCES IN TWO LANDSCAPE MANAGEMENTS AND ONTOGENIC LIGHT REQUIREMENTS OF TERRESTRIAL FERNS IN KEBUN RAYA BATURRADEN, CENTRAL JAVA - Agung Sedayu; Rahadian Ajeng Saraswati; Yuli Puji Astuti (Reinwardtia, 2022)
SEDAYU, A., SARASWATI, R. A. & ASTUTI, Y. P. 2022. Light preferences in two landscape managements and ontogenic light requirements of terrestrial ferns in Kebun Raya Baturraden, Central Java. Reinwardtia 21(1): 25–33. — Human management on landscapes influences environmental requirements including solar irradiation, which may affect fern establishment in different age classes. Two contrasting terrestrial fern communities were inspected in Kebun Raya Baturraden, Central Java; the first thrives among the garden (collection) area, representing the well managed area, and the latter living on the less managed area closest to a natural forest remnant. We found 78.7% species living exclusively in either landscape type; only 21% were shared on both, indicating a light preference among ferns and lycophytes. The four most common species (out of 32 fern and lycophyte species), Cyclosorus heterocarpus, Selaginella ornata, Nephrolepis biserrata, and Sphaerostephanos arbuscula in three different age classes and under gradient canopy openness were surveyed. Statistical test on the canopy openness of individuals of S. ornata and N. biserrata showed that three age categories used significantly different canopy openness, which is not the case for C. heterocarpus and S. arbuscula. It showed that some ferns and lycophytes ontogenically have gradual requirements on light exposure, while others are able to live in wide range of light exposure. This implies that in terms of wild species management, including ferns, the Baturraden gardens landscape management must be directed toward the ecological understanding of species of interest for Botanical Gardens and conservation